Comparison of Various Levels of Parallel Multilevel Active Filter Using NPC Multilevel Inverter - Farouk Hadj Benali; Fouad Azzouz (Institute of Advanced Engineering and Science, 2016)
This paper puts forward the technique of reference signal generation of the reactive instantaneous power and the technique of the SPWM control signal generation of the multilevel active filter. A comparison between the source currents before and after filtering is made. Then a comparison between the different source currents of different multilevel active filters. The subjects of comparison are the total harmonic distortions (THD) of the source current. The obtained simulation results have proved that the filtering quality is improved when increasing the active filter levels. Simulations are carried out by PSIM program.